The effect of different soil moisture conditions on growth and transpiration of Nicotiana Tabacum L. - Wand, W. F.(Werner Friedmar) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. Agric.) -- University of Stellenbosch, 1962.